PENCEGAHAN STUNTING DAN PENINGKATAN GIZI REMAJA MELALUI PENDEKATAN PARTISIPATIF BERBASIS POTENSI LOKAL DI DESA TEGALREJO, KECAMATAN BAYAT, KABUPATEN KLATEN - Atika Rike Arofa; Luthfil Ghozali Ma'nawi; Muhammad Nur Rizkiyanto; Silfiya Ayu Diah Pitaloka; Sofiya Nida Khoirunnisa; Hanif Ula Mas'ud; Annisa Nur Aini; Titania Alya Putri; Lira Fitri Cahya Ningrum; Riska Ayu Safitri; Salsabila Andaluisa; Difa Yeppy Anggara; Ailsa Diah Maharani (JRCE (Journal of Research on Community Engagement), 2025)
Stunting is still one of the serious public health problems in Indonesia with a national prevalence of 24.4% (SSGI 2021). This condition not only has an impact on the child's physical growth, but also decreases cognitive abilities, increases the risk of disease, and reduces productivity in the future. Tegalrejo village, Bayat district, Klaten regency, has a prevalence of under-five nutrition problems of 6.9% with the main challenge being low nutritional literacy in mothers and adolescents. The thematic Kuliah Kerja Nyata (KKN) Thematic Group 020 UIN Raden Mas Said Surakarta was held on June 25-July 31, 2025 with the aim of increasing community nutrition awareness, encouraging the use of local food, and strengthening the role of adolescents in stunting prevention. The method used is descriptive qualitative through observation, interview, Focus Group Discussion (FGD), socialization, and field action based on community-based intervention. The results of the activity showed an increase in public knowledge about balanced nutrition, prevention of anemia in adolescent girls, and utilization of local food potential. Posyandu assistance programs and simple sanitation improvements also contribute to supporting a healthy environment. The implication of this activity is that the participatory approach based on local potential is able to become a sustainable intervention model that can be replicated in other villages to support the national program to accelerate the reduction of stunting.